2009
DOI: 10.1097/dad.0b013e3181888869
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Cutis (Involving Chronic Lymphocytic Leukemia) Within Excisional Specimens: A Series of 6 Cases

Abstract: We present 6 cases of chronic lymphocytic leukemia (CLL) that incidentally involved 6 excisional specimens for biopsy-proven carcinoma. CLL was notably absent from all 5 biopsies that were available for review. In 2 of 6 cases, this was the patients' initial presentation of CLL. Five of 6 cases involved routine paraffin-embedded tissue specimens and 1 case involved frozen tissue sections from a Mohs surgical procedure. The mean age range of the patients was 84 years. Only one of 5 patients in which we have fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 9 publications
1
22
0
2
Order By: Relevance
“…Die B-Lymphoblasten der ALL erweisen sich positiv für CD79a und TdT, T-Lymphoblasten hingegen für CD1a, CD3, CD43 und TdT. Bei der CLL exprimieren die Tumorzellen beispielsweise CD5, CD19, CD20, CD43 und vereinzelt CD5 (Abbildung 9b) [29,32,66,67] [29] (Abbildung 10a). In der Immunhistochemie zeigt sich bei der AML in 50-65 % und bei der CML in 70-80 % der Fälle eine positive NASD-Färbung [29,66].…”
Section: Klinische Befundeunclassified
See 1 more Smart Citation
“…Die B-Lymphoblasten der ALL erweisen sich positiv für CD79a und TdT, T-Lymphoblasten hingegen für CD1a, CD3, CD43 und TdT. Bei der CLL exprimieren die Tumorzellen beispielsweise CD5, CD19, CD20, CD43 und vereinzelt CD5 (Abbildung 9b) [29,32,66,67] [29] (Abbildung 10a). In der Immunhistochemie zeigt sich bei der AML in 50-65 % und bei der CML in 70-80 % der Fälle eine positive NASD-Färbung [29,66].…”
Section: Klinische Befundeunclassified
“…Auch beim rezidivfreien Überleben und der mittleren Zeitdauer der kompletten Remission ergaben sich keine statistisch signifikanten Unterschiede [28]. Andere Arbeitsgruppen konnten keinen direkten Zusammenhang zwischen dem Ausmaß der Hautinfiltration bei LC oder einem spezifischen histologischen Infiltrationsmuster und einer prognostischen Bedeutung herstellen [27,67]. Die molekularpathologische Diagnostik verschiedener Genmutationen (z.…”
Section: Differenzialdiagnosenunclassified
“…Nor were there significant differences in the recurrence-free survival and average duration of complete remission [28]. Other working groups have shown that there is no direct relationship between the extent of infiltration of the skin in LC or a specific histological infiltration pattern and prognostic significance [27,67]. In the future, the molecular pathological diagnosis of various gene mutations (e.g., NPM1, FLT3) will be very important for the pathogenetic interpretation and prognosis of LC and underlying forms of leukemia [33].…”
Section: Therapy and Prognosismentioning
confidence: 99%
“…The B lymphoblasts in ALL are positive for CD79a and TdT, while T lymphoblasts are positive for CD1a, CD3, CD43 and TdT. In CLL the tumor cells may express CD5, CD19, CD20, CD43 and occasionally CD5 (Figure 9b) [29,32,66,67]. The cytologic appearance of individual AML forms is characterized by various monomorphic cell lines, which in myeloblastic leukemia (FAB-M 1 and -M 2 ) are characterized by medium-sized to large mononuclear cells with a light cytoplasm and large, basophilic cell nuclei.…”
Section: Histopathology/cytology/ Immunochemistrymentioning
confidence: 99%
“…[9][10][11][12] An unusual but well-documented presentation is the occurrence of specific B-CLL infiltrates in the vicinity of epithelial and nonepithelial lesions, including squamous cell carcinoma, keratoacanthoma, melanoma, Merkel cell carcinoma, dermatofibroma to name but a few. [13][14][15][16][17][18] Additionally, an association of B-CLL and various cutaneous T-cell lymphomas has been documented, including MF, Sézary syndrome, peripheral T-cell lymphoma involving the skin, and natural killer-cell lymphoma. [19][20][21] Occurrence of leukemic infiltrates on the site of a previous herpes simplex or herpes zoster infection leads to the speculation that specific skin infiltrates of B-CLL can be triggered by antigenic stimulation.…”
Section: Discussionmentioning
confidence: 99%